Financial services firms' criteria for differentiating betweem emerging markets in sub-Saharan Africa - Antrobus, Francis (My University, 2009)
As local legislation and market saturation curtail their growth and profitability, South Africa financial services companies are looking for new markets in Sub Saharan Africa at an astounding rate. This research looks at key attributes of markets within Sub Saharan African countries and analyses how the decision makers within financial services firms priorities these attributes when making expansion decisions in this regard. The research has two main purposes. Firstly, to empower corporate decision makers to quickly analyse all possible markets using readily available data, and in so doing, build a short-list of possible target investment destinations. Further, it aims to guide policy makers for these same countries to create meaningful frameworks that encourage foreign direct investment. Charalambous‟ 2006 qualitative study was used as a basis for this quantitative study. A subset of five of the ten attributes used by Charalambous (2006) were used and an additional attribute recently cited in similar literature were tested in a conjoint study. Convenience sampling with a snowball element was used to gather the respondent data. The questionnaire which was designed on the basis of choice-based conjoint analysis was first subjected to a qualitative pilot phase in which personal interviews were conducted by the researcher in order to screen and validate the questionnaire. The questionnaire was then published on the internet and response data was gathered electronically. There were a total of 30 valid responses. Respondent‟s demographics were widespread across various sub-sectors of the financial services industry. It therefore transpires that some demographic groupings were small in size and hence some caution must be exercised when extrapolating the findings to the population. Data was analysed using Sawtooth™ and NCSS software, interpreted and presented. Key findings from this research include: the top three scoring attributes account for seventy percent of the decision process when financial services firms evaluate iii foreign markets. These attributes are: market size and demand conditions, country governance and political risk, and economic environment and macroeconomic performance. All of these attributes contribute more than twenty percent to the decision. If policy makers want to attract FDI in this sector, favourable policy should be drafted in this regard to ensure maximal attractiveness to the foreign investors.
A research report submitted in fulfillment of the requirements for the Master of Business Administration, in the Faculty of Commerce Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2009
Keywords: Financial services; Emerging markets